Potensi Ekstrak Atuna racemosa sebagai Anti - Methicillin Resistant Staphylococcus aureus (MRSA) - Siti Isrina Oktavia Salasia; Novra Arya Sandi; Fajar Budi Lestari; Verda Farida; Nurbani Aziz (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2017)
Staphylococcus aureus is one of the major causative agents of mastitis in animals and a variety of human diseases such as septicemia, endocarditis, arthritis dan osteomyelitis. Infection of Methicillin-resistant S. aureus (MRSA) has been widely reported and these strains are usually resistant to multiple antibiotics. The purpose of this study was to evaluate the potential of Atuna racemosa, as an alternative herbal medicine against MRSA infection. The MRSA strains were isolated from human and confirmed based on their resistant to various antibiotics and analyzing of the mecA gene by polymerase chain reaction (PCR). Atuna racemosa originated from Ambon, Maluku, Indonesia, were extracted using 70% ethanol. The activities of the Atuna racemosa extract against MRSA were performed by diffusion disc agar and dilussion agar tests. The results showed that Atuna racemosa extract has the barrier effect of MRSA growth at a concentration of 5% in the diffusion test and at a concentration of 7% in the dilution test. Atuna racemosa could be used as an alternative new drugs with dose of 0.07 g/ml (7%) against MRSA which is multi-resistant to many antibiotics.